2002
DOI: 10.1046/j.1365-2621.2002.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and catalytic properties of phytate‐degrading enzymes (phytases)

Abstract: Phytate-degrading enzymes catalyse the step-wise release of phosphate from phytate, the principle storage form of phosphorus in plant seeds and pollen. They are widespread in nature, occurring in plants and micro-organisms, as well as in some animal tissues. Phytate-degrading enzymes have been studied intensively in recent years because of the great interest in such enzymes for reducing phytate content in animal feed and food for human consumption. Phytate-degrading enzymes are also of interest for producing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
219
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(235 citation statements)
references
References 151 publications
(221 reference statements)
8
219
2
6
Order By: Relevance
“…During the germination of cereals, phytate is degraded by intrinsic phytase enzyme (Kumar et al 2010). Naturally, there are dissimilarities in the capacities of various plant and microbial species to dephosphorylate phytate, due to differences in their intrinsic phytatedegrading activities (Egli et al 2002) and the properties of the enzymes, such as protein stability and pH, as well as temperature optimum for phytate degradation (Konietzny and Greiner 2002). The degree of illumination during germination has been found to be an important factor in the reduction of phytates, with germinating under blue or red light being more effective than germinating in the dark (Khattak et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…During the germination of cereals, phytate is degraded by intrinsic phytase enzyme (Kumar et al 2010). Naturally, there are dissimilarities in the capacities of various plant and microbial species to dephosphorylate phytate, due to differences in their intrinsic phytatedegrading activities (Egli et al 2002) and the properties of the enzymes, such as protein stability and pH, as well as temperature optimum for phytate degradation (Konietzny and Greiner 2002). The degree of illumination during germination has been found to be an important factor in the reduction of phytates, with germinating under blue or red light being more effective than germinating in the dark (Khattak et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, dietary myo-inositol phosphates have been suggested to bring about benefits for human health, such as amelioration of heart disease conditions by controlling hypercholesterolemia and atheriosclerosis (14), prevention of renal stone formation (8), and protection against a variety of cancers, in particular colon cancer (31). activity has been detected in plants, micro-organisms, and in some animal tissues (15,30) and phytases from several plant and microbial species have been purified and characterised.…”
Section: Introductionmentioning
confidence: 99%
“…From these studies it was concluded that the phosphate residue at position C-2 of the myo-inositol is resistant to dephosphorylation by phytases (15). There was only one exception reported so far in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic methods of phytate degradation in foods and feeds have gained considerable interest, regarding their numerous advantages over physical or chemical methods (2). Phyta ses, phosphohydrolases of myo-inositol hexakisphosphate, hydrolyse phytate to a pool of lower myo-inositol phosphates (3,4). In breadmaking, phosphorolytic activity originates from wheat or rye fl our enzymes as well as from the yeast phytase (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…There are 3-phytases A (myo-inositol hexakisphosphate 3-phos phohydrolase, EC 3.1.3.8), which start catalytic action at C3 atom of the myo-inositol ring, 6-phytases A (myo-inositol h exaphosphate 6-phosphohydrolase, EC 3.1.3.26), which initiate the hydrolysis at the C6, and phytases B (EC 3.1. 3.2), non -specifi c acid phosphomonoesterases (3). Generally, p hytases A are not able to hydrolyse phosphate residue at the C2 of the myo-inositol ring.…”
Section: Introductionmentioning
confidence: 99%